(untitled) (Ticontre. Theory Text Translation, 2017)
This article aims to trace a history of Italian contemporary poetry from a sociological point of view, using three symbolic dates for its periodization: 1971, 1975, 1979. In 1971, books announcing a new poetic season come out; in 1975 the publication of Il pubblico della poesia shows the disintegration of the literary field; in 1979 the Castelporziano Festival becomes the allegory of a cultural change. These events are closely examined. It will be argued that those years catalysed a transformation in the structure of the public of poetry that lasts until today.